APLIKASI KLINIS N-ACETYLCYSTEINE PADA STROKE ISKEMIK AKUT - Setyopranoto, Ismail; Aifa, Bardatin Lutfi; Satiti, Sekar (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
Pharmacological strategies to enhance reperfusion in acute ischemic stroke currently rely on the use of recombinant tissue plasminogen activator (rtPA), which acts by activating the fibrinolytic cascade. Although its clinical efficacy has been well established, rtPA does not significantly affect the non-fibrin components of thrombi, resulting in relatively low rates of early arterial recanalization (~30%), particularly in cases involving platelet-rich clots. Furthermore, rtPA increases the risk of intracerebral hemorrhage, thereby limiting its overall benefit–risk ratio. Consequently, alternative thrombolytic agents capable of dissolving arterial thrombi without elevating bleeding risk are urgently needed. Von Willebrand factor (vWF) plays a pivotal role in primary hemostasis, and elevated plasma vWF levels are associated with an increased risk of arterial thrombosis. Therapeutic strategies targeting vWF offer a novel approach to lysing platelet-rich thrombi, as their mechanisms operate independently of conventional platelet activation pathways. During arterial thrombosis, vWF multimers mediate platelet cross-linking; thus, proteolysis of vWF has the potential to disrupt platelet-rich thrombi and restore cerebral blood flow. N-acetylcysteine (NAC) cleaves disulfide bonds within vWF multimers, promoting thrombus dissolution and enhancing arterial recanalization. Compared with conventional antithrombotic agents, NAC demonstrates a superior safety profile, even in hemorrhagic stroke models, making it a promising therapeutic candidate for acute ischemic stroke. Moreover, NAC exhibits antioxidant, anti-inflammatory, and neuroprotective effects that support neuronal recovery and improve functional outcomes. Therefore, intravenous NAC may provide dual benefits—as an effective, safe, and affordable thrombolytic and neuroprotective agent—particularly in populations with limited access to rtPA. Keywords: N-acetylcysteine, von Willebrand factor, thrombolytic, neuroprotectant, acute ischemic stroke